Linking green purchasing capabilities to environmental and economic performance: The moderating role of firm size. Issue 4 (October 2018) - Yook, Keun Hyo; Choi, Jeong Hoon; Suresh, Nallan C.
Abstract: This study identifies firms' green purchasing capabilities, classified into operational capabilities and dynamic capabilities, and measures their effects on the environmental and economic performance of a firm. We developed instruments to measure operational green purchasing capabilities and dynamic green purchasing capabilities. This study also investigates the moderating effect of firm size on the relationship between green purchasing capabilities and firm performance. The structural equation model (SEM) is used to analyse 239 responses from Japanese manufacturing companies. The results indicate that their green purchasing capabilities positively affect environmental and economic performance. Operational capabilities and dynamic capabilities have different levels of effects on green purchasing performance. A further analysis of the moderating effect of firm size shows that the high economic performance of green purchasing relies on the level of dynamic capabilities rather than firm size. Highlights: Green purchasing capabilities positively affect environmental and economic performance. Operational capabilities and dynamic capabilities have different impact levels on green purchasing performance Large companies are expected to generate higher performance than small firms due to more resources and leverage. Small companies with a high level of dynamic capabilities indicate high economic performance.